Needs Analysis of The Traffic Safety Training Hyper Content Module at The Ministry of Transportation - Komalasari, Lina; Muslim, Suyitno; Winarsih, Murni (LPPM Undiksha, 2020)
Traffic safety training whose material needed a concrete visualization aspect. To accommodate this, teaching materials were needed to support the learning process. This study aims to describe the results of needs analysis which is the first step of the Research & Development process conducted with a qualitative approach. Data collection techniques are done by conducting research through documentation, observation, and interviews. The results of the needs analysis have been found several problems, that is the heterogeneous characteristics from training participants, limited experience of training participants, limited training time, lack of teaching materials, and training implementation locations throughout Indonesia. Hyper content-based printing modules are a great alternative because they can bring related factual aspects of traffic safety to training participants. In the next research, it is expected to develop a hyper content-based traffic safety training module.